Carbon skeleton supported iron-based electrode and preparation method and application thereof
By using carbon skeleton support and current Joule thermal heating method in the iron-based electrode, electrodes with porous carbon foam loaded with iron element particles were prepared, which solved the problems of complex preparation processes of traditional iron anodes and achieved efficient and energy-saving electrode preparation and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411819908.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The preparation process of traditional iron anode is complex, has high energy consumption, and has serious self-discharge. There are problems such as hydrogen evolution passivation during charging and discharging, which limits its commercial application.
The iron-based electrode is supported by a carbon skeleton, and an electrode with a porous carbon foam structure loaded with iron particles is prepared by using carbon cloth, carbon paper or carbon fiber felt as the carbon support framework material and combined with the rapid heating method of current Joule thermal effect.
It realizes efficient and energy-saving electrode preparation, has excellent conductivity and stability, and has high capacitance in an alkaline environment, which significantly improves the activity of the anode of the iron-nickel battery, reduces energy consumption and increases material utilization.
Smart Images

Figure CN119812177A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a carbon skeleton supported iron-based electrode and a preparation method and application thereof. Background Art
[0002] As an environmentally friendly and efficient energy storage device, aqueous nickel-iron batteries have received widespread attention in recent years. However, the traditional iron anode method often has problems such as complex preparation process, high energy consumption, severe self-discharge, and hydrogen evolution passivation during the charge and discharge process, which limits its commercial application. That is, the existing electrodes not only have a complex preparation process, but also have poor electrochemical performance.
[0003] Therefore, it is particularly important to develop an efficient, energy-saving, and high-performance electrode preparation method. In particular, it is particularly important to provide an efficient electrode preparation method. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a carbon skeleton supported iron-based electrode and a preparation method and application thereof. The carbon skeleton supported iron-based electrode of the present invention has good electrochemical properties, such as high capacitance in an alkaline environment, and the preparation process is efficient and uncomplicated.
[0005] The carbon skeleton supported iron-based electrode described in the present invention is an iron-based electrode with a current collector of a fiber structure such as carbon cloth, carbon paper or carbon fiber felt as a carbon supporting skeleton material. This electrode not only has excellent conductivity and stability, but also can provide sufficient attachment space for the loaded organic matter and iron salt precursor materials. The preparation method described in the present invention is time-saving and has high preparation efficiency. The Joule heat effect of the current quickly heats the sample, so that the iron salt is quickly decomposed into nanoparticles of the iron element. The gas generated during the carbonization of the organic matter guides the precursor to form a porous structure. This porous structure can not only provide a large number of loading sites for the iron element particles, but also provide ion channels during the charge and discharge reaction of the iron-based electrode, which is beneficial to the deep electrochemical reaction of the iron-based electrode material.
[0006] A first aspect of the present invention provides a carbon skeleton supported iron-based electrode.
[0007] Specifically, a carbon skeleton-supported iron-based electrode includes a carbonaceous fibrous current collector, porous carbon foam filled in the gaps of the carbonaceous fibrous current collector, and iron-containing particles supported on the porous carbon foam.
[0008] Preferably, the iron-containing particles account for 8-55% of the total weight of the carbon skeleton-supported iron-based electrode, and more preferably 10-50%, for example 10%, 20%, 30%, 40%, 50%.
[0009] Preferably, the porous carbon foam accounts for 5-25% of the total weight of the carbon skeleton-supported iron-based electrode, and more preferably 10-20%, for example, 5%, 10%, or 20%.
[0010] Preferably, the chemical composition of the iron-containing particles is metallic iron and / or iron oxide.
[0011] Preferably, the carbonaceous fibrous current collector comprises at least one of carbon cloth, carbon paper or carbon fiber felt.
[0012] A second aspect of the present invention provides a method for preparing a carbon skeleton supported iron-based electrode.
[0013] Specifically, a method for preparing a carbon skeleton-supported iron-based electrode comprises the following steps:
[0014] S1, cleaning the carbon fiber current collector as a carbon support skeleton material;
[0015] S2, uniformly coating a mixed solution containing iron salt and carbon foam precursor organic matter on the surface of the cleaned carbon support skeleton material to obtain a material;
[0016] S3. Using the Joule heating effect of electric current to heat-treat the material in step S2 to obtain the carbon skeleton-supported iron-based electrode.
[0017] Preferably, in step S1, the carbon support skeleton material is cleaned by plasma cleaning, and the atmosphere during the plasma cleaning process is argon or air, which removes possible oil stains on the surface of the carbon support skeleton material and increases the surface hydrophilic groups, which is conducive to the uniform loading of subsequent materials.
[0018] Preferably, in step S2, the iron salt includes at least one of ferric chloride, ferrous sulfate and ferric nitrate.
[0019] Preferably, in step S2, the carbon foam precursor organic matter is selected from at least one of polyvinyl pyrrolidone, citric acid, and glucose. These organic matter and iron salt will react chemically in the subsequent Joule heat reaction to form porous carbon foam and iron element particles.
[0020] Preferably, in step S2, the solvent of the mixed solution is at least one of water or ethanol.
[0021] Preferably, in step S2, in the mixed solution, the concentration of the iron salt is 0.1-2.2 mol / L, more preferably 0.1-2 mol / L.
[0022] Preferably, in step S2, in the mixed solution, the concentration of the carbon foam precursor organic matter is 1-500 g / L, more preferably 50-400 g / L.
[0023] Preferably, in step S3, the heating rate of the heat treatment is 500-2000°C / second, the temperature of the heat treatment is 800-1500°C, and the time of the heat treatment is 1-60 seconds; further preferably, the heating rate of the heat treatment is 900-2000°C / second, the temperature of the heat treatment is 900-1300°C, and the time of the heat treatment is 1-10 seconds.
[0024] By electrifying the material in step S2, the sample is quickly heated by the Joule heat effect of the current, so that the iron salt is quickly decomposed into nanoparticles of the iron element, and the organic matter is quickly carbonized, and the gas generated during the carbonization process forms porous carbon foam.
[0025] Step S3 not only enables the organic matter and the iron salt to react rapidly to generate porous carbon foam-loaded iron particles, but also ensures that the reaction product (porous carbon foam-loaded iron particles) fills the gaps in the carbon-supported skeleton material to obtain the carbon skeleton-supported iron-based electrode.
[0026] Preferably, in step S3, the atmosphere of the heat treatment is nitrogen, argon or vacuum.
[0027] A third aspect of the present invention provides an application of a carbon skeleton supporting an iron-based electrode.
[0028] A battery comprises the above-mentioned carbon skeleton supporting an iron-based electrode.
[0029] Preferably, the battery is an iron-nickel battery.
[0030] The above carbon skeleton supports the application of iron-based electrode in the redox reaction of the anode of iron-nickel battery.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] (1) The carbon skeleton supported iron-based electrode of the present invention has good electrochemical properties due to its unique composition and structure, such as high capacitance in an alkaline environment. The activity of the carbon skeleton supported iron-based electrode as an anode of an iron-nickel battery is significantly higher than that of a conventional commercial anode.
[0033] (2) The carbon skeleton supported iron-based electrode of the present invention is prepared by the electric current Joule effect rapid heating method. The preparation method is convenient and the heating speed is extremely fast. The heat treatment time is only a few seconds. It not only improves the preparation efficiency and saves time, but also reduces the energy consumption required for the high-temperature heat treatment process and increases the utilization rate of the anode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope image of the carbon skeleton supporting the iron-based electrode in Example 1;
[0035] Figure 2 This is a scanning electron microscope image of the carbon skeleton supporting the iron-based electrode in Example 1;
[0036] Figure 3 This is a scanning electron microscope image of the carbon skeleton supporting the iron-based electrode in Example 1;
[0037] Figure 4 Comparison of cyclic voltammetry curves of Examples 1-3 and Comparative Examples 1-2 in 4M KOH+0.2M LiOH electrolyte;
[0038] Figure 5 Comparison diagram of constant current charge and discharge curves of Examples 1-3 and Comparative Examples 1-2 in 4M KOH+0.2M LiOH electrolyte;
[0039] Figure 6 This is a comparison chart of the constant current charge and discharge curves of the carbon skeleton supported iron-based electrode before and after the stability test of Example 1. DETAILED DESCRIPTION
[0040] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be noted that the following embodiments do not limit the protection scope of the present invention.
[0041] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0042] The method for preparing a carbon skeleton-supported iron-based electrode provided by the present invention comprises the following steps:
[0043] S1. Cleaning a current collector having a fiber structure such as carbon cloth, carbon paper or carbon fiber felt as a carbon support skeleton material;
[0044] S2, uniformly coating a mixed solution containing iron salt and carbon foam precursor organic matter on the surface of the cleaned carbon support skeleton material to obtain a material;
[0045] S3. Using the Joule heating effect of electric current to perform heat treatment, the material is heated in a short time (only a few seconds) to obtain a carbon skeleton-supported iron-based electrode.
[0046] Example 1
[0047] A carbon skeleton supported iron-based electrode comprises a carbon fiber current collector (carbon paper), porous carbon foam filled in the gaps of the carbon fiber current collector, and iron-containing particles supported on the porous carbon foam.
[0048] A method for preparing a carbon skeleton-supported iron-based electrode comprises the following steps:
[0049] S1. Cut the carbon paper into 3*6cm size and place it in air plasma atmosphere for 60 seconds;
[0050] S2, dissolving 1 mol of ferric chloride hexahydrate and 200 g of polyvinyl pyrrolidone in 1 liter of ethanol to obtain a mixed solution, immersing the carbon paper treated in step S1 in the mixed solution for 5 seconds and then taking it out to dry. To ensure that the mixed solution is evenly coated on the surface of the carbon paper, the above immersion-drying process is repeated 3 times to obtain a material;
[0051] S3. Place the material obtained in step S2 in a Joule heating device under a nitrogen atmosphere for heating treatment, raise the temperature to 1000° C. within 1 second, maintain for 5 seconds, and then cool to room temperature to obtain a carbon skeleton supported iron-based electrode.
[0052] Example 2
[0053] A method for preparing a carbon skeleton-supported iron-based electrode comprises the following steps:
[0054] S1. Cut the carbon cloth into 3*6cm size and place it in air plasma atmosphere for 60 seconds;
[0055] S2, dissolving 1 mol of ferric chloride hexahydrate and 300 g of glucose in 1 liter of water to obtain a mixed solution, immersing the carbon paper treated in step S1 in the mixed solution for 5 seconds and then taking it out to dry, to ensure that the mixed solution is evenly coated on the surface of the carbon paper, the above immersion-drying process is repeated twice to obtain a material;
[0056] S3. Place the material obtained in step S2 in a Joule heating device under a nitrogen atmosphere for heating treatment, heat to 1300° C. within 1 second, maintain for 2 seconds, and then cool to room temperature to obtain a carbon skeleton supported iron-based electrode.
[0057] Example 3
[0058] A method for preparing a carbon skeleton-supported iron-based electrode comprises the following steps:
[0059] S1. Cut the carbon fiber felt into 3*6cm size and place it in air plasma atmosphere for 60 seconds;
[0060] S2, dissolving 1 mol of ferric nitrate hexahydrate and 300 g of polyvinyl pyrrolidone in 1 liter of ethanol to obtain a mixed solution, immersing the carbon paper treated in step S1 in the mixed solution for 5 seconds and then taking it out to dry, to ensure that the mixed solution is evenly coated on the surface of the carbon paper, the above immersion-drying process is repeated 5 times to obtain a material;
[0061] S3. Place the material obtained in step S2 in a Joule heating device under a nitrogen atmosphere for heating treatment, raise the temperature to 900° C. within 1 second, maintain for 10 seconds, and then cool to room temperature to obtain a carbon skeleton supported iron-based electrode.
[0062] Comparative Example 1
[0063] This comparative example provides an iron-based electrode prepared by a conventional method, comprising the following steps:
[0064] S1. Mix commercial ferroferric oxide powder, superconducting carbon black and polyvinylidene fluoride in a weight ratio of 90:6:4, and then grind with N-methylpyrrolidone to obtain a solid concentration of 20 mg mL -1 Mixed slurry;
[0065] S2. Coating the mixed slurry on the surface of carbon paper and drying it to obtain a carbon paper-supported iron-based electrode (also called a traditional commercial anode).
[0066] Comparative Example 2
[0067] A method for preparing a carbon skeleton-supported iron-based electrode comprises the following steps:
[0068] S1. Cut the carbon paper into 3*6cm size and place it in air plasma atmosphere for 60 seconds;
[0069] S2, dissolving 1 mol of ferric chloride hexahydrate in 1 liter of ethanol to obtain a mixed solution, immersing the carbon paper treated in step S1 in the solution for 5 seconds and then taking it out to dry. To ensure that the mixed solution is evenly coated on the surface of the carbon paper, the above immersion-drying process is repeated 3 times to obtain a material;
[0070] S3. Place the material obtained in step S2 in a Joule heating device under a nitrogen atmosphere for heating treatment, raise the temperature to 1000° C. within 1 second, maintain for 5 seconds, and then cool to room temperature to obtain a carbon skeleton supported iron-based electrode.
[0071] Related characteristics test
[0072] 1. Scanning electron microscope analysis:
[0073] The carbon skeleton-supported iron-based electrode prepared in Example 1 was subjected to electron microscopy scanning analysis at different magnifications. The results are as follows: Figure 1 , Figure 2 , Figure 3 As shown. It can be clearly seen that the porous foam loaded with iron particles is loaded on the carbon fiber surface of the carbon paper and fills the gaps between the carbon fibers. This structure is conducive to the rapid transmission of electrons and ions in the electrochemical reaction process of the electrode material. The carbon foam loaded with iron particles is conducive to the ions in the reaction process entering the pores of the porous carbon foam, allowing the iron element in the electrode to fully participate in the reaction.
[0074] 2. Electrochemical performance test of carbon skeleton supported iron-based electrode:
[0075] The carbon skeleton-supported iron-based electrodes prepared in Examples 1, 2 and 3, the iron-based electrode prepared by conventional method in Comparative Example 1, and the iron-based electrode without porous carbon foam in Comparative Example 2 were electrochemically tested in 4M KOH+0.2M LiOH electrolyte ("M" represents the concentration unit "mole / liter").
[0076] The electrochemical test results are as follows Figure 4 , Figure 5 As shown by Figure 4 (“Current density” indicates current density, and “Potential (V) vs. Hg / HgO” indicates the potential relative to the Hg / HgO electrode) It can be seen that: when the iron element loading on the electrode is normalized, the carbon skeleton-supported iron-based electrodes prepared in Examples 1-3 all have relatively obvious redox peaks and good polarization phenomena in the cyclic voltammetry test. At the same time, compared with Comparative Examples 1 and 2, the cyclic voltammetry curve area of the carbon skeleton-supported iron-based electrodes prepared in Examples 1-3 is obviously larger.
[0077] Depend on Figure 5 ("Potential" means electric potential, "Specific capacity" means specific capacity) It can be seen that: under the condition of normalizing the iron content on the electrode, the carbon skeleton supported iron-based electrodes prepared in Examples 1-3 all have good capacitance in the constant current charge and discharge test, and compared with Comparative Example 1 and Comparative Example 2, the capacitance of the carbon skeleton supported iron-based electrodes prepared in Examples 1-3 is also significantly improved.
[0078] Figure 6 This is a comparison chart of the constant current charge and discharge test before and after the cycle stability test of Example 1. Figure 6 (“Potential” means potential, “Specific capacity” means specific capacity) It can be seen that there is no obvious attenuation of the electrode capacity before and after the stability test (200 cycles), indicating that the electrode prepared by this method has good stability.
[0079] Therefore, the carbon skeleton supported iron-based electrodes prepared in Examples 1-3 have more superior electrochemical performance than Comparative Examples 1 and 2.
[0080] The above electron microscope scanning and electrochemical performance test data show that the iron-based electrode based on carbon skeleton support prepared by the present invention has porous carbon foam loaded with iron element particles filling the gaps between carbon fibers, and has excellent polarization performance and capacitance. In addition, the iron-based electrode based on carbon fiber skeleton support prepared by the present invention has stable structure and performance, low cost, and effectively overcomes the problems of hydrogen evolution passivation and cumbersome laboratory preparation process and poor bonding of existing commercial iron-nickel battery anodes.
[0081] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A carbon skeleton supported iron-based electrode, characterized in that: The invention comprises a carbon fiber current collector, porous carbon foam filled in the gaps of the carbon fiber current collector, and particles containing iron elements supported on the porous carbon foam.
2. The carbon skeleton supported iron-based electrode according to claim 1, characterized in that: The iron-containing particles account for 8-55% of the total weight of the carbon skeleton-supported iron-based electrode.
3. The carbon skeleton supported iron-based electrode according to claim 1, characterized in that: The porous carbon foam accounts for 5-25% of the total weight of the carbon skeleton-supported iron-based electrode.
4. The carbon skeleton supported iron-based electrode according to claim 1, characterized in that: The chemical composition of the particles containing the iron element is metallic iron and / or iron oxide.
5. The carbon skeleton supported iron-based electrode according to claim 1, characterized in that: The carbonaceous fibrous current collector includes at least one of carbon cloth, carbon paper or carbon fiber felt.
6. The method for preparing a carbon skeleton-supported iron-based electrode according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, cleaning the carbon fiber current collector as a carbon support skeleton material; S2, coating a mixed solution containing iron salt and carbon foam precursor organic matter on the surface of the cleaned carbon support skeleton material to obtain a material; S3. Using the Joule heating effect of electric current to heat-treat the material in step S2 to obtain the carbon skeleton-supported iron-based electrode.
7. The preparation method according to claim 6, characterized in that: In step S1, the carbon support skeleton material is cleaned by plasma cleaning, and the atmosphere during the plasma cleaning process is argon or air.
8. The preparation method according to claim 6, characterized in that: In step S2, the iron salt includes at least one of ferric chloride, ferrous sulfate, and ferric nitrate; and / or the carbon foam precursor organic matter is selected from at least one of polyvinyl pyrrolidone, citric acid, and glucose; and / or, in the mixed solution, the concentration of the iron salt is 0.1-2.2 mol / L; and / or, in the mixed solution, the concentration of the carbon foam precursor organic matter is 1-500 g / L.
9. The preparation method according to claim 6, characterized in that: In step S3, the heating rate of the heat treatment is 500-2000°C / second, the temperature of the heat treatment is 800-1500°C, and the time of the heat treatment is 1-60 seconds; and / or the atmosphere of the heat treatment is nitrogen, argon or vacuum.
10. A battery, characterized in that: The invention comprises a carbon skeleton-supported iron-based electrode as described in any one of claims 1 to 5.